Macmillan end of life discharge pilot project at the James Cook university hospital (JCUH). Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Taylor, Yvonne; Walker, Jane; Hunter, Noeleen; Harris, Andrea; Nicholson, Alexander
Abstract : Background: Current end of life initiatives emphasise the importance of achieving the preferred place of care for patients approaching end of life. National survey data suggest 50–60% patients would prefer a home death but data for South Tees indicates that only 22% of patients achieve this (2007–2009). A new service was therefore developed to offer consultation and support to effect a safe, coordinated and patient-focused discharge to every patient on the end of life care pathway (EOLCP) whose preferred place of care was not JCUH. Aims: To increase the awareness, expertise and confidence of the host clinical teams in discharging these complex patients. Methods: Funding was secured from Macmillan Cancer Support to employ a Discharge Sister with administrative support. During a 3-month development phase, project promotion and stakeholder liaison (within and beyond the acute hospital) was prioritised. Thereafter every ward was contacted every day to offer the service to patients on the EOLCP. Discharge packs comprising discharge prescription, medication administration charts, patient/carer information and discharge checklist were designed for every community care location served by JCUH as a tertiary centre. Results: In the first 12 months, 111 dying patients were discharged home via the project. Awareness and confidence of the discharge logistics process continue to increase among ward staff but negotiating the plan seems to require the greater experience of the Macmillan discharge sister and specialist palliative care team (SPCT) colleagues. Conclusion: A bespoke discharge pathway and experienced facilitation secures rapid discharge of a complex vulnerable patient group. Although there are no previous data for comparison the 'clinical memory' of the SPCT (who previously supported these discharges in an ad hoc fashion) suggests significantly increased activity. The authors conclude that more patients are achieving their preferred place of death. The work continues and is subject to independent evaluation.